2019
DOI: 10.1002/jsfa.9516
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between quantitative descriptive analysis and flash profile in profiling the sensory properties of commercial red sufu (Chinese fermented soybean curd)

Abstract: BACKGROUND Red sufu is a type of sufu produced by solid‐state fermentation of soybean curd and coloration with red mold rice. The purposes of this study were: (i) to characterize commercial red sufu samples using the quantitative descriptive analysis (QDA) and flash profile (FP) by ten trained and ten untrained panelists, respectively; (ii) to compare the differences in panel performance, descriptive abilities and sensory maps between the two methodologies; and (iii) to compare the efficiency between QDA and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…P7 positively correlated with most of the physicochemical characteristics, making it significantly different from other FHV beer samples. e ellipse constructed with sample loadings showed that P7 was substantially different from other FHV beer samples as its ellipse has no overlap with those of other FHV beer samples [48].…”
Section: Physiochemical Properties Of Beermentioning
confidence: 97%
“…P7 positively correlated with most of the physicochemical characteristics, making it significantly different from other FHV beer samples. e ellipse constructed with sample loadings showed that P7 was substantially different from other FHV beer samples as its ellipse has no overlap with those of other FHV beer samples [48].…”
Section: Physiochemical Properties Of Beermentioning
confidence: 97%
“…The performance of the panellists was estimated by Generalized Procrustes analysis (GPA). A low residual variance (<2), scaling factors (near 1), and overlapped positions of variables and products obtained by the 12 panellists from the GPA indicated that high levels of group homogeneity were procured [27]. After the group panellists reached high levels of agreement, three sessions were performed, and 6 roasted lamb samples (1 dummy sample + 5 test samples) were evaluated at each session.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Quantitative descriptive analysis (QDA) is an important tool in the study of food flavor, through the collection, counting and analysis of sensory data from participants, and ultimately the quantification of the flavor characteristics of the food (Adriana et al, 2021; He & Chung, 2018). The quantitative indicators measured by the commonly used chemical methods cannot fully explain the interaction of various sensory elements, so sensory evaluation plays an irreplaceable role in the food industry.…”
Section: Introductionmentioning
confidence: 99%